Shear avalanches in plastic deformation of a metallic glass composite. (February 2016) - Tong, X.; Wang, G.; Yi, J.; Ren, J.L.; Pauly, S.; Gao, Y.L.; Zhai, Q.J.; Mattern, N.; Dahmen, K.A.; Liaw, P.K.; Eckert, J.
Abstract: Changes in intermittent shear avalanches during plastic deformation of a Cu50 Zr45 Ti5 (atomic percent) alloy in response to variant structures including fully glassy phase and/or nanocrystal/glass binary phase are investigated. Second crystalline phases are introduced into the glassy-phase matrix of a Cu50 Zr45 Ti5 metallic glass to interfere with the shear-avalanche process, which can release the shear–strain concentration, and then tune the critically-dynamic behavior of the shear avalanche. By combining microstructural observations of the nanocrystals with the statistical analysis of the corresponding deformation behavior, we determine the statistic distribution of shear-avalanche sizes during plastic deformation, and established its dependence on the geometric distribution of nanocrystals. The scaling behavior of the distribution of shear-avalanche sizes follows a power–law relation accompanied by an exponentially-decaying scaling function in the pure metallic glass, and the metallic glass containing the small nanocrystals, which can be described by the mean-field theory. The large shear-avalanche events are dominated by structural tuning-parameters, i.e., the resistance of shear banding, and the size and volume fraction of the second crystalline phase in metallic glasses. Highlights: A plastic medium is introduced into the glassy phase to tune the shear avalanche. The serrated flow in plastic regime of the CuZrTi alloy is statistically analyzed. The geometric distribution of second phase dominates the shear avalanche. The statistical distribution of shear-avalanche size follows power–law relationship. Twinning in nanoscale can influence the shear-avalanche size in the CuZrTi alloy.